Assessing the Impact of Renewable Energy in Mitigating Climate Change: A Comprehensive Study on Effectiveness and Adaptation Support - Abidi, Ilyes; Nsaibi, Mariem (International Journal of Energy Economics and Policy, 2024)
The objective of this study is to evaluate the effectiveness of renewable energy in combating climate change and supporting adaptation efforts. By applying the ARDL model to data from 58 countries spanning the period from 1990 to 2022, this study sheds light on the opportunities and challenges associated with this involved relationship. The results indicate that renewable energy plays a significant role in reducing greenhouse gas emissions and mitigating temperature anomalies. Specifically, wind energy, biomass, geothermal energy, solar energy, and waste utilization demonstrate a positive correlation with greenhouse gas emission reduction. Moreover, wind energy, solar energy, waste utilization, and the proportion of renewable energy in primary energy consumption are also linked to a decrease in temperature anomalies. These findings emphasize the importance of implementing concrete measures such as promoting sustainable transportation, ensuring sustainable management of natural resources, raising awareness and enhancing education, increasing subsidies and incentives for renewable energy and strengthening regulations on greenhouse gas emissions.